2011
DOI: 10.1002/nag.910
|View full text |Cite
|
Sign up to set email alerts
|

Stress–dilatancy and force chain evolution

Abstract: SUMMARYThe evolution of internal structure plays a pivotal role in the macroscopic response of granular materials to applied loads. A case in point is the so-called 'stress-dilatancy relation', a cornerstone of Soil Mechanics. Numerous attempts have been made to unravel the connection between stress-dilatancy and the evolution of fabric and contact forces in a deforming granular medium. We re-examine this connection in light of the recent findings on force chain evolution, in particular, that of collective for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…These force chains are supported laterally by a complimentary weak network of particles [13]. Prior to collapse force chains accumulate stored potential energy and this process continues until the force chains reach their peak load, after which buckling occurs and the force chains experience a loss in load-carrying capacity [14]. Furthermore, Tordesillas & Muthuswamy [15] showed that force chain buckling can be elastic or plastic depending on the state of the contact points.…”
Section: Simulation Parameters and Specimen Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…These force chains are supported laterally by a complimentary weak network of particles [13]. Prior to collapse force chains accumulate stored potential energy and this process continues until the force chains reach their peak load, after which buckling occurs and the force chains experience a loss in load-carrying capacity [14]. Furthermore, Tordesillas & Muthuswamy [15] showed that force chain buckling can be elastic or plastic depending on the state of the contact points.…”
Section: Simulation Parameters and Specimen Generationmentioning
confidence: 99%
“…On the other hand, at low friction some of the strong force chains can yield while others have not reached the limiting value for sliding, hence yielding is more gradual. Earlier research [14] has showed that void spaces are created between the particles in the buckling chain and their laterally supporting neighbours and Only a limited amount of information is provided by scalar measures of the material fabric such as Z. A deeper understanding can be gained using orientation data that can be quantified using the fabric tensor, defined by Satake [11] as:…”
Section: Simulation Parameters and Specimen Generationmentioning
confidence: 99%
“…Dilatancy implies that the shear strength partly stems from the work against pressure that is necessarily spent in order to shear the granular material. The idea is often invoked to justify * emilien.azema@univ-montp2.fr † franck.radjai@univ-montp2.fr ‡ jean-noel.roux@ifsttar.fr semiempirical stress-dilatancy relations [4] between ϕ and ψ, which numerical and micromechanical investigations [5][6][7][8][9] sought to support and to relate to internal state characteristics (such as fabric or force chains). In dense granular assemblies subjected to quasistatic shear under constant normal stress σ yy , ϕ, as a function of growing shear strain γ , first increases to a maximum (the peak deviator stress, typically reached for strain γ peak of the order of 10 −2 ), and then decreases to a final plateau (in the so-called critical state of soil mechanics [4]).…”
mentioning
confidence: 99%
“…The properties of frictionless grains might be correctly described by constitutive models involving numerically measured relations between stresses and microscopic variables such as coordination and fabric [46]. They are nevertheless expected to set an important constraint to first-principle approaches attempting to predict internal friction and dilatancy properties from microscopic rheophysical mechanisms [5,8,9] (see [42] for more comments).…”
mentioning
confidence: 99%
“…Many numerical studies employ the discrete element method (DEM) for this particular problem (e.g., Ferdowsi et al, 2013;Morgan, 2004;Tordesillas et al, 2011), a numerical technique that is ideally suited to investigate the behavior of aggregates with a large number of degrees of freedom. By implementing the appropriate physical interactions between particles, DEM can be employed to simulate 10.1029 and generalize the complex behavior observed in the laboratory, and test hypotheses regarding the mechanisms of stick-slips.…”
Section: Introductionmentioning
confidence: 99%